Kompresi Citra Medis dengan DWT dan Variable Length Code - Garnita Darma Putri, I Gusti Ayu; Sastra, Nyoman Putra; Widyantara, I Made Oka; Wiharta, Dewa Made (Majalah Ilmiah Teknologi Elektro, 2021)
This paper designed a medical image compression scheme using DWT with mother wavelet Coiflet and Symlet. Thresholding and quantization process are the key to lossy compression in this scheme, and the outputs will be coded with Huffman or Arithmetic coding. There are four different codec combinations namely: Coiflet-Huffman, Coiflet- Arithmetic , Symlet-Huffman, Symlet- Arithmetic . Compression performance of each codec will be analyzed based on PSNR and compression ratio. The compression testing used 3 grayscale medical images with dimension of 160x160 pixels. The most optimal PSNR dan rate are produced by Symlet-Aritchmetic codec with recommendation threshold value less than 12. Threshold value above 12 causes PSNR of the reconstruction image will be below the minimum PSNR stardard for digital image, which is of 30dB.